PENGARUH KEDISIPLINAN TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN AKIDAH AKHLAK KELAS X MA AN-NUR BULULAWANG - Dayu Irmawan; Ika Ratih Sulistiani; Mohammad Eko Nasrulloh (VICRATINA, 2022)
This study was conducted to determine the effect of discipline on student learning outcomes in the tenth grade Akhidah Akhlaq subjects at MA An-Nur Bululawang. Discipline is a condition created by a training process that is developed into a series of behaviors and in it there are elements of obedience, obedience, order that must be carried out with full responsibility. Learning outcomes are a change in behavior, knowledge and attitudes obtained by someone after carrying out the process of learning activities at school. This research is a type of survey research, using a quantitative descriptive approach where the instrument and data collection uses a closed questionnaire with a Likert scale score assessment, and documentation. The population of class X MA An-Nur Bululawang is 155 students and in taking the sample using a simple random sampling technique using the Slovin formula, the research sample data is 61 students. Testing the data analysis used in this study, namely normality test, linearity test, and for hypothesis testing using simple linear regression test. Class X MA An-Nur Bululawang".